2021
DOI: 10.1519/jsc.0000000000002699
|View full text |Cite
|
Sign up to set email alerts
|

Running Demands and Activity Profile of the New Four-Quarter Match Format in Men's Field Hockey

Abstract: Ihsan, M, Yeo, V, Tan, F, Joseph, R, Lee, M, and Aziz, AR. Running demands and activity profile of the new four-quarter match format in men's field hockey. J Strength Cond Res XX(X): 000-000, 2018-This study determined the running demands of men's field hockey with regards to the revised four-quarter match format. Twenty-eight male field hockey players were equipped with global positioning system units while competing in 14 competitive international games over a 1-year period. All matches allowed for unlimited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 30 publications
5
49
2
Order By: Relevance
“…In the forward position, differences between high-intensity accelerations (0.9 n·min) and decelerations (1.0 n·min) were trivial, suggesting that some forward players may complete more high-intensity accelerations than decelerations during match play. Previous studies have also shown that forward positions accelerate to higher intensities more frequently than defenders and midfielders [79, 80]. This difference could be due to the unlimited interchange rule that reduces effective playing time; meaning less total distance and energy is expended, therefore allowing a higher intensity intermittent profile to be maintained [79].…”
Section: Discussionmentioning
confidence: 99%
“…In the forward position, differences between high-intensity accelerations (0.9 n·min) and decelerations (1.0 n·min) were trivial, suggesting that some forward players may complete more high-intensity accelerations than decelerations during match play. Previous studies have also shown that forward positions accelerate to higher intensities more frequently than defenders and midfielders [79, 80]. This difference could be due to the unlimited interchange rule that reduces effective playing time; meaning less total distance and energy is expended, therefore allowing a higher intensity intermittent profile to be maintained [79].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the differences observed between strikers, midfielders, and defenders with respect to playing time spent in postures between 10 and 40°o f torso flexion are related to the role-specific tasks performed by these athletes, and the associated competing affordances presented to them. Performing in a high-intensity, intermittent sport, field hockey athletes must cover ground quickly (16,27) and may adopt more upright torso postures to do this efficiently. In addition, owing to the 360°nature of the game, they are required to visually explore the playing environment, and more upright postures maximize their ability to move the head and torso to orient their visual field to the horizon line.…”
Section: Playing Positionmentioning
confidence: 99%
“…This drop-off has been suggested to be related to the transient fatigue experienced throughout the game [18]. To further examine the fluctuations of running performance during the game, several team sports have further analysed the match-play running performances by smaller segments [19][20][21][22]. Dividing the match into quarters allowed coaches to identify where the temporal decrements exist [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%